Application of the Project Based Learning Learning Model to Improve Students' Learning Ability Through Collaborative Activities in English Subjects for Class XI Mechanical Engineering Students at SMK Negeri 2 Samarinda - Samsiyah, Samsiyah (Educationist: Journal of Educational and Cultural Studies, 2022)
This research was classified as a learning practice in Best Practice which was carried out at SMK Negeri 2 Samarinda in class XI TP (machining technique) of the first semester in the academic year 2022/2023. This study aimed at imrpving students’ ability in learning English particularly in learning procedure text through the use of Best Practice Procedures consisted of planning, application, observation and reflection. Atthe end of the text learning procedure that applied the Project Based Learning (PjBL) method, the results showed that (1) Students became more motivated and active in learning; (2) Learning carried out by applying the PjBL method increased the ability of students to transfer knowledge and collaborate attitudes among friends; (3) the application of the PjBL learning method can improve the ability of students to think critically smoothly. This can be seen from the level of participation of students in organizing projects such as managing time, finding resources, solving problems they encounter in project completion and this will add to their learning experience; (4) The application of this PjBL learning method can train and improve the abilities of students in communication both in the process of making projects and in reporting the results obtained; (5) learning atmosphere was more fun and challenging; and (6) By collaborating with other subjects, this applied method can streamline time and tasks done by students. The conclusion obtained was that the application of the Project Based Learning learning model can improve the learning ability of students in English learning about Procedure text.